The Association Between Physical Activity and Insulin Level Under Different Levels of Lipid Indices and Serum Uric Acid - Lin, Yajuan; Fan, Rui; Hao, Zhujing; Li, Jiatian; Yang, Xiaolei; Zhang, Ying; Xia, Yunlong (Frontiers in Physiology, 2022)
Objectives: Insulin resistance (IR) has been shown to play important role in the pathogenesis of type 2 diabetes mellitus (T2DM). There is an intricate interplay between IR, dyslipidemia, and serum uric acid (SUA) in people with and without diabetes. Physical activity has a positive impact on insulin sensitivity in insulin resistant populations. However, the effect of different intensities of physical activity on insulin levels under different lipid indices and SUA levels is unclear. Methods: To explore the association between physical activity and insulin, we enrolled 12982 participants aged above 18 years from the National Health and Nutrition Examination Survey (NHANES) conducted between 2009 and 2018. Next, we conducted multivariate logistic regression analyses, generated fitted smoothing curves, and visualized the data using generalized additive models. Results: Increased intensities of physical activity can significantly reduce insulin levels. The association between physical activity and insulin persisted even after adjusting for confounding factors, with β value (95%CI) = -17.10 (-21.64, -12.56) in moderate group, β value (95%CI) = -28.60 (-33.08, -24.11) in high group, respectively. High-intensity physical activity significantly lowered insulin levels in the lower and higher SUA tertiles, and three tertiles of LDL-c, HDL-c, TG. Moreover, the link between physical activity and insulin was stronger in male individuals. Conclusions: This study shows that physical activity can significantly lower insulin levels, and high-intensity physical activity still has additional potential benefits for insulin levels, even in the condition of dyslipidemia and hyperuricemia.